2011
DOI: 10.1002/jcb.23141
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor retinoid-related orphan receptor α1 modulates the metabolic activity of human osteoblasts

Abstract: Nuclear receptor retinoid-related orphan receptor alpha (RORα1) is a member of ROR-family receptors. It is broadly expressed in various tissues and organs during embryonic development. However, so far, little is known about its function in bone. Here, we have elucidated the expression and function of RORα1 in human MG-63 osteoblast-like cells. Reverse transcriptase-polymerase chain reaction and immunocytochemical analysis revealed that human MG-63 osteoblasts expressed and produced RORα1. Other cell lines, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…The transcription factors, such as RORA, STAT1, STAT5a, and CEBP, act in regulation of reactive oxygen species production, 19 apoptosis, 20 immunity, 21 and inflammatory response. 22 …”
Section: Resultsmentioning
confidence: 99%
“…The transcription factors, such as RORA, STAT1, STAT5a, and CEBP, act in regulation of reactive oxygen species production, 19 apoptosis, 20 immunity, 21 and inflammatory response. 22 …”
Section: Resultsmentioning
confidence: 99%
“…Results of genome-wide association studies (GWAS) or GWAS meta-analyses have demonstrated that RORA is one of the primary risk factors for cardiovascular metabolism ( 29 ). Additionally, RORA serves a role in the regulation of the inflammatory response ( 30 ). In the current study, the expression of RORA was downregulated, which suggested that RORA may be associated with MI.…”
Section: Discussionmentioning
confidence: 99%
“…RORβ has been shown to suppress mineralization and to decrease expression of Bglap (encoding osteocalcin) and Sp7 (encoding osterix) mRNA in cultured murine osteoblasts (52). RORα has been shown to be involved in osteoblast metabolism and RORα-deficient mice have abnormal bone development (53, 54). …”
Section: Retinoid Receptorsmentioning
confidence: 99%